Aluminum-Doped Zinc Oxide as Front Electrode for Rear Emitter Silicon Heterojunction Solar Cells with High Efficiency - Daniel Meza; Alexandros Cruz; Anna Belen Morales-Vilches; Lars Korte; Bernd Stannowski (Applied Sciences, 2019)
Transparent conductive oxide (TCO) layers of aluminum-doped zinc oxide (ZnO:Al) were investigated as a potential replacement of indium tin oxide (ITO) for the front contact in silicon heterojunction (SHJ) solar cells in the rear emitter configuration. It was found that ZnO:Al can be tuned to yield cell performance almost at the same level as ITO with a power conversion efficiency of 22.6% and 22.8%, respectively. The main reason for the slight underperformance of ZnO:Al compared to ITO was found to be a higher contact resistivity between this material and the silver grid on the front side. An entirely indium-free SHJ solar cell, replacing the ITO on the rear side by ZnO:Al as well, reached a power conversion efficiency of 22.5%.